Morphological and Morphometric Identification of Amphibians (Rana) in Meurandeh Dayah Village, Langsa City - Miduk Leonardo Tambun; Lusi Selvina Hutabarat; Sirem Suri; Nuryati; Siti Rhadiatun Mardiah; Ayu Wahyuni (Jurnal Biologi Tropis, 2023)
Amphibians, categorized as vertebrate animals and characterized as poikilotherms, comprise three main groups known as Caudata, Gymnophiona, and Anura, with the latter commonly recognized as frogs or toads. The objective of this study is to examine the morphology and morphometrics of various frog species in Meurandeh Dayah Village, Langsa City. The research employs quantitative methods to facilitate a comparative analysis of each sample. The findings reveal the presence of six shutter species: Fejervarya cancrivora, Hylarana macrodactyia, Rana erythraea, Hylarana nicobariensis, Hyperolius horstockii, and Hylarana erythraea. The morphometric measurements conducted on these Rana species demonstrate distinctive morphological variations among them.